Beowulf opera scenes: classroom music pedagogy and knowledge when composing an opera with primary-school children - Axtell, I; Anderson, A; MacGregor, E; Nenadic, E; Fautley, M; Evans, N (SAGE Publications, 2024)
Composing with children is a complex area that many generalist primary-school teachers in England report finding challenging or intimidating. This article draws on existing literature relating to composing in schools, child-centered learning, cultural capital, and classroom pedagogy to situate and discuss a longitudinal research project exploring composing with primary-aged children. The article focuses on one of eight schools involved in the project, in which children worked with a professional composer alongside their regular classroom teacher to compose operatic scenes to accompany the epic poem, Beowulf. The project utilized a collaborative action research framework, featuring researcher observations of the six composing sessions, semi-structured interviews and reflections with the teacher and composer, and a focus group with the children. The findings highlight seven themes relating to children’s understandings of the composing process, which are theorized into conceptualizations of musical knowledge. The article concludes by tracing some of the international implications for children composing in primary-school contexts.